2010
DOI: 10.1071/wfv19n8_fo
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires in boreal ecosystems: past, present and some emerging trends

Abstract: Abstract. With the emergence of a new forest management paradigm based on the emulation of natural disturbance regimes, interest in fire-related studies has increased in the boreal forest management community. A key issue in this regard is the improvement of our understanding of the variability in past disturbances and its linkages with climate and ecosystems. The surge in research activity has further been exacerbated by the increasing awareness of climate change, which has already exposed boreal forests to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This is especially true given current stand conditions that promote more damaging wildfires, such as high surface fuel loads and high densities of younger trees (ladder fuels) and snags (Agee & Skinner, ). Similar effects of changing climate–fire dynamics have been found throughout western forests, including the Sierra Nevada (Littell et al ., ), as well as in boreal systems (Girardin et al ., ), south African systems (Archibald et al ., ), and projected globally (Gonzalez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true given current stand conditions that promote more damaging wildfires, such as high surface fuel loads and high densities of younger trees (ladder fuels) and snags (Agee & Skinner, ). Similar effects of changing climate–fire dynamics have been found throughout western forests, including the Sierra Nevada (Littell et al ., ), as well as in boreal systems (Girardin et al ., ), south African systems (Archibald et al ., ), and projected globally (Gonzalez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence of an increase in AAB or overall number of fires per year in the NWT Taiga Shield since the start of fire records in 1965, consistent with Rickbiel, Hermosilla, Coops, White, and Wulder (). However, many studies have shown or predicted an increase in AAB and fire frequency in Canadian boreal forests, primarily due to increased summer drought conditions (Flannigan, Krawchuk, deGroot, Wotton, & Gowman, ; Gillett, Weaver, Zwiers, & Flannigan, ; Girardin, Ali, & Hély, ; Kasischke & Turetsky, ). The susceptibility of forests in our study area to frequent and large fires appears to be influenced more by the effects of temperature on fuel dryness, than by precipitation despite similar precipitation levels as those reported by Larsen () and McCoy and Burn ().…”
Section: Discussionmentioning
confidence: 99%
“…Lena Pillars, which was a Nature Park since 1994, was nominated World Heritage Site in 2012, is the youngest of the 201 protected areas analysed in this study. Most of the forest loss occurred in this area in -2004and 2011), when it was already protected (but before the establishment of the World Heritage Site in 2012). However, in 2013 (just one year after its nomination by UNESCO) and then in 2016 and 2018, high other-than-fire loss peaks were recorded.…”
Section: Lena Pillars World Heritage Sitementioning
confidence: 99%
“…In the last decades, however, large areas of Russian boreal forests have been damaged by different factors (mainly logging and fires), which led to significant forest loss (Girardin et al, 2011;Pyzhev et al, 2021). Boreal forests in Russia play a crucial role in climate change because they are an important carbon sink, holding almost 50% of the northern hemisphere's terrestrial carbon.…”
Section: Introductionmentioning
confidence: 99%